Brief Assessment of Impaired Cognition (BASIC)—Validation of a new dementia case‐finding instrument integrating cognitive assessment with patient and informant report. (19th August 2019) - Jørgensen, Kasper; Nielsen, T. Rune; Nielsen, Ann; Waldorff, Frans Boch; Høgh, Peter; Jakobsen, Søren; Gottrup, Hanne; Vestergaard, Karsten; Waldemar, Gunhild
Abstract : Objectives: The aim of this study was to develop and validate a new brief and accurate case‐finding instrument for dementia and cognitive impairment. Previous research indicates that combining cognitive tests with informant and/or patient report may improve accuracy in dementia case‐finding. The Brief Assessment of Impaired Cognition (BASIC) integrates these three sources of information. Methods: BASIC was prospectively validated in five memory clinics. Patients consecutively referred from general practice were tested at their initial visit prior to diagnosis. Control participants were primarily recruited among participating patients' relatives. Expert clinical diagnosis was subsequently used as gold standard for estimation of the classification accuracy of BASIC. Results: A very high discriminative validity (specificity 0.98, sensitivity 0.95) for dementia (n = 122) versus socio‐demographically matched control participants (n = 109) was found. In comparison, the MMSE had 0.90 specificity and 0.82 sensitivity. Extending the discriminative validity analysis to cognitive impairment (both dementia and MCI, n = 162) only slightly reduced the discriminative validity of BASIC whereas the discriminative validity of the MMSE was substantially attenuated. Administration time for BASIC was approximately 5 minutes compared with 10 to 15 minutes for the MMSE. Conclusions: BASIC was found to be an efficient and valid case‐finding instrument for dementia and cognitive impairment in a memory clinic setting.